2013
DOI: 10.1097/mbp.0b013e32835ebbb5
|View full text |Cite
|
Sign up to set email alerts
|

The independent relationship of epicardial adipose tissue with carotid intima-media thickness and endothelial functions

Abstract: Our study showed that EAT is an independent factor of adverse changes in CIMT, FMD, and PWV. Future studies, investigating the vascular influence of EAT at the molecular level, may provide therapeutic options to prevent its adverse vascular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
(28 reference statements)
2
18
0
1
Order By: Relevance
“…The EFT was an independent associate in multiple logistic regression analysis. In addition, CIMT was also shown to correlate with EFT in previous studies (23, 24). As the subjects in the AI group were hormonally inactive and traditional cardiovascular risk factors were similar between groups, we can speculate that increased epicardial fat tissue may be responsible for these early cardiac and vascular changes.…”
Section: Discussionsupporting
confidence: 56%
“…The EFT was an independent associate in multiple logistic regression analysis. In addition, CIMT was also shown to correlate with EFT in previous studies (23, 24). As the subjects in the AI group were hormonally inactive and traditional cardiovascular risk factors were similar between groups, we can speculate that increased epicardial fat tissue may be responsible for these early cardiac and vascular changes.…”
Section: Discussionsupporting
confidence: 56%
“…In contrast, adiponectin which has antiatherogenic properties through improvement of endothelial function and anti-inflammatory effect was shown to be under expressed in EAT in patients with CAD (16). In the light of these findings, EAT is associated with metabolic syndrome (17), insulin resistance (17, 18), endothelial dysfunction, subclinical atherosclerosis (19) and overt atherosclerotic CAD (20). …”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis has been identified as an inflammatory disease, 30 and it has been shown that epicardial adipose tissue is associated with 3 , 31 33 but not specific to atherosclerosis, as the recent literature suggests that it is also higher in patients with atrial fibrillation, heart failure, and hypertension 34 36 . Bachar et al 32 showed that asymptomatic patients with coronary artery disease (CAD) have significantly more epicardial adipose tissue than patients without CAD.…”
Section: Discussionmentioning
confidence: 99%